Neuronal Activity in the Rostral Superior Colliculus Related to the Initiation of Pursuit and Saccadic Eye Movements - Krauzlis, Richard J. (J Neurosci, 2003)
The extinction of the central fixated stimulus before the appearance of a new target stimulus reduces the latency of saccades and pursuit, a phenomenon known as the “gap effect.” The superior colliculus (SC) plays a prominent role in the gap effect for saccades, and recent data indicate that this structure also plays some role in the control of pursuit. We now show that the firing rate of buildup neurons in the rostral SC exhibits a gap effect during the initiation of both pursuit and saccadic eye movements to parafoveal targets. Most neurons exhibited an increase in tonic activity starting ∼100 msec after the offset of the fixation spot, regardless of whether the target later appeared inside or outside of the response field of the neuron. The subsequent appearance of the target in the response field evoked phasic increases in activity that were approximately twice as large as the effects on tonic activity. For both pursuit and saccades, the levels of tonic and phasic activity were inversely correlated with latency on a trial-by-trial basis. These changes in activity provide a neuronal correlate for the shared effects on latency observed previously with the gap paradigm for pursuit and saccades. Finally, the phasic activity at pursuit onset exhibited a gap effect just like the target-evoked response, whereas the burst activity at saccade onset was fixed in amplitude. These results suggest how SC neurons may coordinate the initiation of pursuit and saccades: buildup activity may gate the initiation of pursuit, whereas it indirectly triggers saccades by recruiting a saccade-related burst.